Host response during Yersinia pestis infection of human bronchial epithelial cells involves negative regulation of autophagy and suggests a modulation of survival-related and cellular growth pathways - Alem, Farhang; Yao, Kuan; Lane, Douglas; Calvert, Valerie; Petricoin, Emanuel F.; Kramer, Liana; Hale, Martha L.; Bavari, Sina; Panchal, Rekha G.; Hakami, Ramin M. (Frontiers in Microbiology, 2015)
Yersinia pestis (Yp) causes the re-emerging disease plague, and is classified by the CDC and NIAID as a highest priority (Category A) pathogen. Currently, there is no approved human vaccine available and advances in early diagnostics and effective therapeutics are urgently needed. A deep understanding of the mechanisms of host response to Yp infection can significantly advance these three areas. We employed the Reverse Phase Protein Microarray (RPMA) technology to reveal the dynamic states of either protein level changes or phosphorylation changes associated with kinase-driven signaling pathways during host cell response to Yp infection. RPMA allowed quantitative profiling of the signaling network changes in human lung epithelial cells at different times post infection and in response to different treatment conditions, which included infection with the virulent Yp strain CO92, infection with a derivative avirulent strain CO92 (Pgm- , Pst-), treatment with heat inactivated CO92, and treatment with LPS. Responses to a total of 111 validated antibodies were profiled, leading to discovery of 12 novel protein hits. The RPMA analysis also identified several protein hits previously reported in the context of Yp infection. Furthermore, the results validated several proteins previously reported in the context of infection with other Yersinia species or implicated for potential relevance through recombinant protein and cell transfection studies. The RPMA results point to strong modulation of survival/apoptosis and cell growth pathways during early host response and also suggest a model of negative regulation of the autophagy pathway. We find significant cytoplasmic localization of p53 and reduced LC3-I to LC3-II conversion in response to Yp infection, consistent with negative regulation of autophagy. These studies allow for a deeper understanding of the pathogenesis mechanisms and the discovery of innovative approaches for prevention, early diagnosis, and treatment of plague.